THE EFFECT OF REPLACEMENT COMMERCIAL RATION WITH BREAD WASTE ON COMMERCIAL CARCASS PIECES OF KAMPUNG UNGGUL BALITNAK (KUB) CHICKENS - M. R., Damanik; Siti, N. W.; Sukmawati, N. M. S. (Jurnal Peternakan Tropika, 2022)
This study aimed to determine the effect of replacement commercial rations with bread waste on commercial carcass pieces of Kampung Unggul Balitnak (KUB) chickens. This research was carried out for 8 weeks in the cage owned by Mr. Gede Suarta which is located on Gulingan Village, Mengwi District, Badung Regency, Bali. The experimental design used was a completely randomized design (CRD) consisting of 3 treatments and 5 replications, so there were 15 experimental units. Each experimental unit contained 2 heads KUB chickens aged of one week with a body weight range of 44 ± 2 g. The treatments were: KUB chickens fed 100% commercial 511 ration without bread waste (P0), KUB chickens fed 75% commercial 511 ration + 25% bread waste (P1), and KUB chickens fed 50% commercial 511 ration + 50% waste bread (P2). The variables observed were carcass weight, carcass percentage, thigh percentage, drumsticks percentage, wings percentage, chest percentage, and back percentage. The results showed that KUB chickens fed 75% commercial rations + 25% of bread waste (P1) and 50% commercial rations + 50% of bread waste (P2) had a carcass weight significantly (P<0.05) lower than P0 treatment (100% commercial ration) of 16.05% and 23.16% respectively, but the percentage of carcass and commercial carcass pieces (thighs, drumsticks, chest, wings, and back) were equal among all treatments (P>0.05). The conclusion of this study is that the replacement of commercial rations with bread waste as much as 25% and 50% in KUB chickens can produce a percentage of carcasses and commercial pieces of carcass (upper thigh, lower thigh, chest, wings, and back) equal to 100% commercial rations, but in carcass weight decreases. Keywords: KUB chickens, carcass weight, commercial carcass pieces, bread waste